Pendekatan Konseling Behavioral pada Kasus Dugaan Ujaran Kebencian dan Penodaan Agama Yahya Waloni - Oktaviawati, Monita (Institut Agama Islam Negeri Curup, 2024)
This research aims to discuss the behavioral counseling approach that focuses on the case of hate speech and blasphemy against Yahya Waloni that sparked public debate. In behavioral theory humans are seen as neutral beings who are not good and not bad so that behavioral counseling centers on individuals to produce more positive behavioral changes. This research uses descriptive qualitative with library research-based data collection methods with descriptive collaboration methods the author explains about hate speech and its impact on religious harmony in Indonesia. The results show that the behavioral counseling approach can be an effective method because it focuses on behavior modification and encourages positive change. This approach centers on the stimulus and individual response to situations to reduce aggressive behavior.